Implementasi Kebijakan Program Pamsimas dalam Mendukung Pencapaian SDGs 6 di Desa Mentaras, Kecamatan Dukun, Kabupaten Gresik - Ahmad Zaki Ardio Putra; Alifah Rahmaniah; Indah Prabawati3; Firre An Suprapto (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Although Indonesia has integrated SDG 6 goals into national development planning, access to safe drinking water and sanitation remains a challenge in rural areas, particularly due to suboptimal policy implementation at the local level. The PAMSIMAS program is a government policy designed to improve access to clean water and sanitation services thru a community empowerment approach. This research aims to analyze the implementation of the PAMSIMAS program policy in supporting the achievement of SDG 6 in Mentaras Village, Dukun District, Gresik Regency. The research approach is descriptive qualitative with data collection thru observation, interviews, and documentation. The analysis was conducted using George C. Edwards III's policy implementation model, which includes communication, resources, executor disposition, and bureaucratic structure. The research results show that the program implementation has achieved significant progress, marked by an increase in the number of households accessing clean water, affordable service costs, and community-based management thru BP-SPAMS and BUMDes that reflect the principle of accountability. However, the implementation of the program still faces challenges such as limited service coverage, an imbalance in the facilitator-to-beneficiary ratio, and coordination obstacles among implementing stakeholders. Therefore, strengthening the dimensions of communication, resources, and institutional coordination is necessary to enhance the effectiveness of program implementation and support the achievement of SDG 6 targets by 2030.